An Initiative Towards the Global Lighting Challenge for Kuwait*. Issue 3 (1st March 2019) - AlNakib, Dina; Al-Ragom, Fotouh; AlOsaimi, Sarah
ABSTRACT: Lighting accounts for 15% of global electricity consumption and contributes to 5% of global greenhouse gas emissions. In the 6th Clean Energy Ministerial (CEM) meeting, an initiative of COP21, Global Lighting Challenge (GLC) was endorsed by 13 countries including the USA and the European Commission. Currently 17 nations have joined this initiative that targets transitioning to energy efficient lighting. Kuwait is among the highest per capita annual energy consumption countries. Kuwait consumes an average of 15 MWh/person/year surpassing industrialized countries. The high consumption pattern is attributed to subsidized electrical energy prices reaching up to 95%. The subsidy endured by the Kuwaiti Government is around 58 billion (USD) for some commodities including fuel and energy for the years 2016 through 2019. This monetary burden, with the current low oil prices, leads to a deficit in the national budget. The Kuwaiti Cabinet endorsed a plan to rationalize fuel prices while the electrical energy prices will be rationalized in some sectors. The residential sector will be the last sector to be considered to avoid political pressure. To join in the global efforts in transitioning to energy efficient lighting, this article assessed the savings realized by replacing incandescent lamps, still used in Kuwait, with LEDs. The savings are estimated for the replacement of 10 lamps per home across 100, 000 homes. The simple payback period for the Kuwaiti government is 9 months if the lamps are distributed free of charge. The savings are estimated at a cost of electrical energy of 0.10/kWh. An economically justified solution for the Kuwaiti government is provided to rationalize national energy consumption, reduce power demand, enhance consumer energy efficiency awareness and most importantly contributing to global efforts in transitioning to efficient lighting.